Iron indices in adults with sickle cell nephropathy in Lagos, Nigeria - Orolu, Muyideen; Mabayoje, Monica; Braimoh, Rotimi; Bello, Babawale Taslim; Amira, Christiana Oluwatoyin; Kushimo, Oyewole; Anyanwu, RA (African Journal of Nephrology, 2022)
Introduction: Although several studies have explored iron indices in patients with sickle cell anaemia (SCA), there is a paucity of evidence regarding the iron status of patients with sickle cell nephropathy (SCN). This study evaluated the range of iron status of adult SCA patients with or without nephropathy in Lagos, Nigeria. Methods: This was a cross-sectional study performed at the Sickle Cell Clinic of the Lagos University Teaching Hospital (LUTH). Patients who were aged 18–65 years were assessed for SCN by determining the albumin-to creatinine ratio (UACR) on a spot urine sample, and determining the estimated glomerular filtration rate, using the CKD–EPI formula, on a steady-state serum creatinine concentration. Iron indices including serum ferritin, serum iron and total iron-binding capacity (TIBC) were measured, and percentage transferrin saturation (TSAT) was calculated. Data were analysed with the Statistical Package for the Social Sciences (SPSS) version 23. Results: A total of 200 patients were included, of whom 119 had SCN. There were no statistically significant differences in iron indices in participants with or without SCN. The median serum ferritin and TSAT of patients with SCN were 265 ng/mL and 31.8%, respectively, while the values were 255 ng/mL and 33.5% in those without SCN, respectively. Few participants were noted to have iron overload based on ferritin and TSAT values, regardless of SCN diagnosis. Although not statistically significant, females tended to have higher ferritin and serum iron values compared to males, irrespective of the presence or absence of SCN; whereas females without SCN had statistically significant higher TSAT values compared to males without SCN (36.2 ± 15.0% and 28.8 ± 11.5%, P = 0.03). Conclusion: Although iron overload is common in patients with SCA, our findings indicate that patients with SCN may require routine evaluation of iron indices because few were iron overloaded. For this reason, the evaluation of iron indices in patients with SCN should be individualised to guide the direction of care and improve clinical outcomes.